The Effectiveness of ICT Integration to Improve Students’ Achievement in EFL Context - Siti Yulaichah; atik rokhayani; diah kurniati (SIMPLE: International Journal of English Education, 2026)
This study aims to identify and analyze the specific difficulties faced by fifth-semester students of the English Education Department at Universitas Muria Kudus during their tour guide simulation in the Intercultural Communication class. The research focuses on linguistic and non-linguistic obstacles that hinder students from communicating effectively while explaining local cultural values and historical sites in English. A descriptive qualitative approach was employed. Data were collected through questionnaires and semi-structured interviews. The findings reveal that grammar was the most dominant difficulty, followed by pronunciation and vocabulary limitations. Affective factors such as nervousness and lack of self-confidence also influenced students’ performance.